Autocorrelation based channel estimation method for space-time block coding system - YING Ren-dong; XU Guo-zhi (Tongxin xuebao)
An autocorrelation based method was proposed to estimate the channel of the space-time block coding（STBC） system.It is shown that when the inputted symbol vector is spatially white,the autocorrelation of the received signal has specific structure due to the orthogonal property of STBC system.From the eigenvector of the autocorrelation matrix,the channel information can be estimated up to a scalar.When the autocorrelation matrix satisfies certain condition,the esti-mation procedure could be further simplified and the channel was obtained directly from the autocorrelation matrix without any matrix inverse or decomposition operation.